2024
DOI: 10.1186/s13756-024-01385-6
|View full text |Cite
|
Sign up to set email alerts
|

Resident-, prescriber-, and facility-level factors associated with antibiotic use in long-term care facilities: a systematic review of quantitative studies

Aurélie Bocquier,
Berkehan Erkilic,
Martin Babinet
et al.

Abstract: Background Antimicrobial stewardship programmes are needed in long-term care facilities (LTCFs) to tackle antimicrobial resistance. We aimed to identify factors associated with antibiotic use in LTCFs. Such information would be useful to guide antimicrobial stewardship programmes. Method We conducted a systematic review of studies retrieved from PubMed, Cochrane Library, Embase, APA PsycArticles, APA PsycINFO, APA PsycTherapy, ScienceDirect and Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…A systematic review of AMS in long-term care facilities in France found that the volume of antibiotic prescriptions was positively associated with staff turnover and after-hours medical practitioner visits, which could be corrected by an on-site coordinating physician [151]. Likewise, a multifaceted intervention for AMS in different parts of the world resulted in either reduction of treatment duration [152,153] or in better informed choice of OAT [137,138].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of AMS in long-term care facilities in France found that the volume of antibiotic prescriptions was positively associated with staff turnover and after-hours medical practitioner visits, which could be corrected by an on-site coordinating physician [151]. Likewise, a multifaceted intervention for AMS in different parts of the world resulted in either reduction of treatment duration [152,153] or in better informed choice of OAT [137,138].…”
Section: Discussionmentioning
confidence: 99%